2008
DOI: 10.1055/s-2007-992933
|View full text |Cite
|
Sign up to set email alerts
|

Statins in the Treatment of Polycystic Ovary Syndrome

Abstract: Many women of reproductive age are affected by polycystic ovary syndrome (PCOS), a heterogeneous endocrinopathy characterized by androgen excess, chronic oligo-anovulation and/or polycystic ovarian morphology. In addition, PCOS is often associated with insulin resistance, systemic inflammation and oxidative stress which, on one hand, lead to endothelial dysfunction and dyslipidemia with subsequent cardiovascular sequelae and, on the other hand, to hyperplasia of the ovarian theca compartment with resultant hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 166 publications
(164 reference statements)
0
32
0
1
Order By: Relevance
“…It has been shown that several circulating markers of oxidative stress are abnormal in women with PCOS, independent of weight excess (187). Oxidative stress in PCOS may participate in systemic inflammation and together with insulin resistance and consequent hyperinsulinaemia promote ovarian thecal compartment dysregulation and dysfunction of endothelial cells, resulting in hyperandrogenism, anovulation and CV disorders (188).…”
Section: Role Of Lipo-oxidative Stressmentioning
confidence: 99%
“…It has been shown that several circulating markers of oxidative stress are abnormal in women with PCOS, independent of weight excess (187). Oxidative stress in PCOS may participate in systemic inflammation and together with insulin resistance and consequent hyperinsulinaemia promote ovarian thecal compartment dysregulation and dysfunction of endothelial cells, resulting in hyperandrogenism, anovulation and CV disorders (188).…”
Section: Role Of Lipo-oxidative Stressmentioning
confidence: 99%
“…[Diamanti-Kandarakis et al 2008;Kodaman and Duleba, 2008a] The insulin resistance and hyperinsulinaemia pathophysiologically implicated in the metabolic and reproductive abnormalities of PCOS [De Leo et al 2003;Nestler, 1997] are the two major facets of the metabolic syndrome (MS) [Reaven, 1988]. MS is characterized by a cluster of metabolic disturbances, such as central obesity, impaired glucose tolerance, dyslipidemia and hypertension that are related to increased cardiovascular risk [Schneider et al 2006].…”
Section: The Effects Of Old New and Emerging Medicines On Metabolic mentioning
confidence: 99%
“…They also express anti-oxidant, antiflammatory and antiprolifarative effects [Kodaman and Duleba, 2008a;Wassmann et al 2002] and together with the lipid reduction these alterations can have a beneficial effect on the long-term cardiovascular morbidity and mortality associated with PCOS ( Figure 2). …”
Section: Statinsmentioning
confidence: 99%
“…However, it is difficult at present to understand whether the oxidative stress or hyperandrogenemia is the initiating factor. Oxidative stress is accepted as the triggering factor for thecal androgen production in PCOS [23]. But the effect of androgens on the pathogenesis of atherosclerosis in different sexes is controversial [24].…”
Section: Cardiovascular Risks Have Been Shown To Be Increased Among Pmentioning
confidence: 99%